Current accounts dynamics in OECD and EU acceding countries - an intertemporal approach - Matthieu Bussière; Marcel Fratzscher; Gernot J. Müller (European Central Bank (ECB), 2004)
The paper extends the standard intertemporal model of the current account to include two important stylised facts: (1) the persistence of current account positions and (2) the relevance of the fiscal balance. Specifically, the paper derives a closed form solution for consumption in the presence of habit persistence and liquidity constraints, which allows us to obtain a dynamic model for the current account where fiscal deficits have an effect. The model is estimated for a panel of 33 countries, including the ten EU acceding countries and structural current account positions are derived. A parsimonious specification including relative income, relative investment and the fiscal balance explains well past current account developments. A key finding of the paper is that, from an intertemporal perspective, current accounts in most acceding countries are currently broadly in line with their structural current account positions.
Keywords: F32; F41; 330; current account; habit persistence; liquidity constraints; panel